The Hierarchy of Needs and Personalities of Characters in the Novel Luka Cita by Valerie Patkar - Siti Solekhah; Yessi Fitriani; Puspa Indah Utami (Journal of Social Work and Science Education, 2026)
This study aims to describe the portrayal of Abraham Maslow’s hierarchy of needs and Sigmund Freud’s tripartite personality structure within the characters of Valerie Patkar’s novel Luka Cita. Employing a descriptive qualitative method, the research used documentation for data collection, with the novel as the primary source. Data were analyzed through content analysis to identify and interpret the relevant psychological constructs. The analysis confirms the presence of both theoretical frameworks. All five stages of Maslow’s needs physiological, safety, love/belonging, esteem, and self-actualization are gradually fulfilled by the characters. Simultaneously, the interaction of Freud’s id, ego, and superego structures forms the internal conflicts driving character development. The research provides a novel, dual-theory psycho-literary analysis of a contemporary Indonesian novel, concurrently applying Maslow’s humanistic and Freud’s psychodynamic theories to interpret character motivation and conflict. The study demonstrates a replicable framework for literary criticism, enabling educators and scholars to conduct structured psychological analyses of character development in narrative fiction. It contributes to cross-cultural literary psychology by validating the applicability of these foundational Western psychological theories to modern Indonesian literature, enriching the interpretation of its thematic depth and character complexity.